Use of a video game based balance training intervention on the balance and function of children with developmental disabilities - Siconolfi-Morris, Gina Cecilia (ProQuest Dissertations & Theses, 2012)
Many children with developmental disabilities (DD) have physical impairments and limitations in their participation. Rehabilitation research often focuses on either physical impairments or participation restrictions, when both need to be investigated. The purposes of these two studies were to evaluate an at home therapist directed video game balance training intervention on balance, gait velocity (GV), hip strength and activities of children with DD. The pilot study was a single-subject non-concurrent multiple baseline design. Balance measures included: weight bearing symmetry; center of pressure area and velocity; time to boundary mean minima and standard deviation; and timed up and go. The participant's enjoyment and perceived difficulty was also explored. Five children (7 to 10 years) with cerebral palsy (CP) participated in a 6 week, 30 minute intervention 3 times per week, with four preselected balance games. Minimal improvements were found in balance, GV, and hip strength, and participants reported the intervention enjoyable and challenging. Three of five participants had significant increases in activities, as measured by the Activities Scale for Kids (ASK). The second study expanded on pilot study results and included 5 children (5 to 10 years) with different diagnoses. Another non-concurrent multiple baseline design was utilized, and the same measures of balance were used except single leg stance time was substituted for timed up and go. No changes were made to the intensity of intervention, but two games were added to the repertoire. There were minimal changes in balance and hip strength; and no changes were found in the ASK. A majority of participants increased GV, and reported the intervention was enjoyable and challenging. Positive changes were found in the combined results for: center of pressure area with eyes open and closed; time to boundary mean minima with eyes closed in the anterior-posterior direction; and GV. These studies suggest this intervention was insufficient to make improvements in the majority of balance measurements and hip strength for children with DD. Increased activities in children with CP were found in the pilot study. These results suggest video game balance training alone for children with DD was insufficient to demonstrate clinically meaningful change. KEYWORDS: Balance, Developmental Disabilities, Gait Velocity, Hip Strength, Activities and Participation